The new face of power of the 21ST century: technology and data - Fakhouri, Luis Gustavo Perez (2022)
This work discusses the influence of technology and data on geopolitics. There is a huge effort by some countries to develop and control some technologies that have the power to impact society as it is currently known. The focus will be on presenting some of these technologies, which actors are leading the area, and its effects. For this, the work is divided into four sections: the first explains the possibilities of using 5G and how it can affect the way of life of societies and also the consequences of its implementation. The second section discusses cyber warfare and which national states have the capabilities for this type of conflict. The third section is about the use of Artificial Intelligence and the technological development strategy of the superpowers. And in the fourth section, it presents the challenges of this dispute over technology and data for countries and companies. The work concludes that if there is not an extraordinary event capable of uniformly accelerating the level of technological development and innovation, countries that do not master technological capabilities will become dependent on the superpowers. This is because the use of technology and data will be converted into economic, political and military power. Thus, geopolitics can be determined by a few countries, which will have a large number of actors surrounding their area of influence.